2022
DOI: 10.26434/chemrxiv-2022-zd9l7-v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A High-Throughput Platform for Efficient Exploration of Functional polypeptides Chemical Space

Abstract: Rapid and in-depth exploration of the chemical space of high molecular weight synthetic polypeptides via the ring-opening polymerization (ROP) of N-carboxyanhydride (NCA) is a viable approach towards protein mimics and functional biomaterials. The traditional synthetic workflow, however, has been labour-intensive and with limited throughput. Here, we develop an efficient chemistry for the high throughput diversification of polypeptides based on a click-like reaction between selenolate and various electrophiles… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…It was found that steric hindrance did not affect the reaction efficiency, as demonstrated by the formation of 4 and 5 in excellent yields. Dialkyl diselenides were also applicable to this transformation, and symmetrical dialkyl monoselenides were obtained in 60%-95% yields (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). Various functionalities (e.g., halogen, ester, nitrile, ether, alkyne and alkene) were well tolerated, showcasing the robustness of this protocol.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…It was found that steric hindrance did not affect the reaction efficiency, as demonstrated by the formation of 4 and 5 in excellent yields. Dialkyl diselenides were also applicable to this transformation, and symmetrical dialkyl monoselenides were obtained in 60%-95% yields (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). Various functionalities (e.g., halogen, ester, nitrile, ether, alkyne and alkene) were well tolerated, showcasing the robustness of this protocol.…”
Section: Resultsmentioning
confidence: 94%
“…[21][22][23][24][25] The oxidant-induced selenoxide elimination as a key step has found wide applications in the total synthesis of drugs and natural products. [26][27][28][29] The subsequent development of reductive systems such as Ph 3 SnH, 30 LiBHEt 3 , 31 Fig. 1 Selected important organoselenium compounds.…”
Section: Introductionmentioning
confidence: 99%
“…While certain synthetic conditions might produce roughly alternating, gradient, or block structures, the precise arrangement of constitutional units within any given macromolecule is unknown, and there will be a distribution of structures produced. 104 Despite the inherent ambiguity, there is considerable interest in the surrogate modeling of such copolymers as they are also the most likely to be experimentally synthesized in quantities amenable to machine learning, 17,18,69,105 at least in the near-term. In recognition that polymers are stochastic molecules that constitute an ensemble of structures, Lin and co-workers have extended the simplified molecular-input line-entry system into the BigSMILES language, which can describe polymers of varying chemistry and architectures.…”
Section: Machine Learning Quantitative Structure−property Relationshi...mentioning
confidence: 99%
“…While certain synthetic conditions might produce roughly alternating, gradient, or block structures, the precise arrangement of constitutional units within any given macromolecule is unknown, and there will be a distribution of structures produced . Despite the inherent ambiguity, there is considerable interest in the surrogate modeling of such copolymers as they are also the most likely to be experimentally synthesized in quantities amenable to machine learning, ,,, at least in the near-term. In recognition that polymers are stochastic molecules that constitute an ensemble of structures, Lin and co-workers have extended the simplified molecular-input line-entry system into the BigSMILES language, which can describe polymers of varying chemistry and architectures. , In principle, BigSMILES strings or other syntactical approaches augmented with other relevant information (e.g., average mole fractions of consitutional units) might be tokenized or processed into numerical encodings for machine learning in a manner similar to small molecules, but there are few demonstrations of syntax-directed machine learning for copolymers.…”
Section: Machine Learning Quantitative Structure–property Relationshi...mentioning
confidence: 99%
“…[22][23][24] More importantly, polypeptides can be synthesized from Ncarboxyanhydride (NCA) ring-opening polymerization in kilogram-scale and offer considerable chemical diversity of side groups. [25][26][27][28][29][30] Fluorescent polypeptides, possessing the similar primary and secondary structures as uorescent proteins, are the ideal candidates for the applications as biomedical uorescent probes. In the last few years, CL was observed among synthetic polypeptides.…”
Section: Introductionmentioning
confidence: 99%